INFLUENCE OF SERVICE QUALITY AND DRUG AVAILABILITY ON PATIENT SATISFACTION THROUGH PATIENT TRUST MEDIATION - Winggia Antena; Rahayu Puji Suci; Anif Prasetyorini; Adya Hermawati; Emma Budi Sulistiarini (Yayasan Adra Karima Hubbi, 2026)
Research Objective: This study intends to investigate and explain the impact of service quality and medicine availability on patient satisfaction, both directly and indirectly, using patient trust as a mediating variable at RSUD Natuna’s Pharmacy Installation. Research Type: This study is quantitative explanatory research. Data were collected through questionnaires distributed to 100 outpatient respondents. The data analysis technique used was Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), implemented in SmartPLS. Research Findings: The results indicate that service quality positively impacts patient trust and satisfaction. The availability of drugs has been demonstrated to boost patient trust, although it has no significant direct impact on patient satisfaction. Furthermore, patient trust was found to positively affect satisfaction and to successfully mediate the relationship between service quality and satisfaction. However, trust cannot mediate the relationship between medicine availability and patient satisfaction, as low medicine stock acts as a physical barrier that cannot be compensated for by the emotional factor of trust alone.